Resistance in Series Model for Ultrafiltration of Betacyanin from Hylocereus Polyrhizus Peels - Azimah, Saman; Mimi Sakinah, A. M. (Asian Network for Scientific Information, 2014)
This study investigates the fouling mechanism in ultrafiltration membrane during separation of betacyanin from Hylocereus Polyrhizus extract. The Resistance-In-Series Model was used to identify the responsible hydraulic resistance. The resistance against the flux was assumed to be comprised as membrane hydraulic, adsorption, pore plugging and fouling resistance. The profile of total resistance and corresponding flux decline were calculated and compared with the experimental data. The result showed that the adsorption resistance (Rad) was the main contributed the rate of flux decline. Moreover the significant organic fouling that contribute during betacyanin separation revealed that the fouling potential was Rad >Rpp > RF. the measured flux recovery of filtration betacyanin production was 65%.